If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + 4k) + -3 = 0 (1 * 4 + 4k * 4) + -3 = 0 (4 + 16k) + -3 = 0 Reorder the terms: 4 + -3 + 16k = 0 Combine like terms: 4 + -3 = 1 1 + 16k = 0 Solving 1 + 16k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 16k = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 16k = 0 + -1 16k = 0 + -1 Combine like terms: 0 + -1 = -1 16k = -1 Divide each side by '16'. k = -0.0625 Simplifying k = -0.0625
| 5((1/2)-3) | | (12x+66)+(2x+20)=9 | | 2(3f+1)= | | -6(1+6x)-1= | | 4n+3(6n-1)=-135 | | 5(1/2-3) | | 2x-17=7x+12 | | 10x+9=7x+8 | | 8p+4=7+7p | | cx+b=5(x-c) | | 4-(3n-3)= | | -14y+28+6x=-44 | | -5*a+(-5*b)=3 | | 32+0.25y=50 | | log(x)=-22.7 | | 1/2•32= | | -268=12(x)-4 | | 8b+8(1-8b)= | | -268=4-12(x) | | 5/9x3/15 | | F(3)=1/2•32 | | 2x+-9(2)=9 | | 4-12(x)=-268 | | 2x+-9(0)=9 | | 9(12/7)+7= | | .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 |